آليات الحجاج اللغوية في سورة يوسف - بن سالم, عميري, هارون نصر (University of El-oued, 2021)
With this wide openness of the field of pilgrims, our study came to pay tribute to the previous Hajj studies in general, and the Holy Qur'an especially as a rhetorical genre different from the rest of the other discourses based and based, especially in its persuasive and Hajj aspect, in order to show the validity of his logic and the depth of his explanation...), It is these linguistic mechanisms that earn the text a high degree of persuasion and influence in The receiver. ممخص البحث: ستقطبً ا ، ة خلاؿ العقكد الأخيرة أضحت حقلا مستقلا َّ ارسات الحجاجي ً ٌ الد َّإف نفتاح الكاسع لمجاؿ ً تخصصات مختمفة مف الأدب كالفمسفة كالمسانيات كالمنطؽ كمع ىذا الا الحجاج جاءت دارستنا تثميننا لما سبقيا مف الدارسا كالقرآف الكريـ خاصة ، ة عامة َّ ت الحجاجي ا يختمؼ ِّ عتباره جنسنا خطابي ً با ن ة الخطابات الأخرل بناء َّ عف بقي خاصة في جانبو ،كمقامنا ختيارنا عمى سكرة ً فكقع ا ، حتى نستبيف صحة منطقو كعمؽ بلاغتو ، الإقناعي كالحجاجي شتممت عميو ىذه السكرة مف آليات ً يكسؼ عميو السلاـ لما ا ة متنكعة( ركابط كعكامؿ َّلغكي ة مف الإقناع َّ ة ىي التي تكسب النص درجة عالي َّ كىذه الآليات المغكي ،)... ألفاظ تعميؿ ،ةَّحجاجي والتأثير في المتمقي.
Keywords: الحجاج